Bilateral Mycobacterium chelonae Keratitis after Phacoemulsification Cataract Surgery. (6th November 2017) - Martinez, Jaime D.; Amescua, Guillermo; Lozano-Cárdenas, Jesus; Suh, Leejee H.
Abstract : The purpose of this manuscript is to report the case of an 81-year-old patient who presented with bilateral keratitis after phacoemulsification surgery. Cultures came back positive for Mycobacterium chelonae . Despite aggressive topical and systemic antimicrobial treatment, the patient developed a corneal perforation in both eyes, treated with corneal glue in the right eye and corneoscleral patch in the left eye. After two years of follow-up, patient was free of infection in the right eye with visual acuity of 20/200 and the left eye progressed to phthisis bulbi. We present an unusual case of bilateral Mycobacterium chelonae keratitis associated with phacoemulsification cataract surgery. This case represents the importance of making clinicians aware of this devastating infection and highlights the need for better management to improve outcomes.